Technology of Fully-mechanized Top Coal Caving Face Passing Through Mine Abandoned Roadway in Chengzhuang Coal Mine - DU Hailong (Meikuang Anquan, 2020)
For the characteristics of the two empty lanes which are parallel empty roadways in front of 3311 fully mechanized caving face in Chengzhuang Mine and empty roadway in roof, and the problems that overhanging support pressure overlaps, the mine pressure appears severely and the roof collapses, etc, filling empty lane is a reasonable way to pass empty lane. The numerical simulation is used to compare and analyze the damage of surrounding rock under the support of different strength filling bodies. It is determined that the filling body strength of the empty road filling to meet the supporting conditions is not less than 2 MPa, and the water-cement ratio of the high water material is determined to be 3∶1. In combination with the actual situation on the site, a reasonable empty road grouting replacement scheme was designed for working face continuously through two roof empty lanes, and industrial tests were carried out. The results show that there is no significant difference between the working face over-the-airway stage and the normal mining stage, and there is no obvious phenomenon of rib spalling and roof caving.